Stabilisasi dan Transportasi Neonatus - Kadir, Minerva Riani (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Approximately 10 percent of newborns will require some level assistance with breathing, and a few (<1 percent) will require resuscitation in the birthing room. After resuscitation, many of these newborns require acute transport to a different facility. Stabilisation prior to transport is essential and the principles of neonatal transportation are independent of distance. Hypothermia and hypoglycaemia should be prevented in neonates during transport as they adversely affect the outcome. This article provides an overview of principles from the STABLE Program, which guides clinicians in providing postresuscitation care and pretransport and during transport stabilization for compromised newborns.